Geochemical Evaluation of Organic Matter Enrichment in the "Mississippian Limestone" Interval of the Anadarko Shelf of Oklahoma. (January 2022) - Adeboye, O.O.; Riedinger, N.; Quan, T.M.
Abstract: Samples from a cored petroleum exploration well drilled in Kingfisher County, Oklahoma were studied using a combination of organic carbon stable isotopes (δ 13 Corg ), and specific elemental geochemical proxies, to determine the effects of paleoproductivity and detrital input on organic matter enrichment in the Mississippian Limestone interval of the Anadarko Shelf. Total organic carbon (TOC) values are between 0 and 2.1 wt %, with an average of 0.4 wt % in the studied interval of the core, while δ 13 Corg values were between −38.6‰ and −24.7‰ (average −28.3 ± 2.9‰). Elemental proxies of detrital input and paleoproductivity are not enriched above average carbonate values, suggesting that there was low nutrient contribution to the study area, and consequent low organic matter productivity during deposition of Mississippian Limestone sediments. Together, insights from our geochemical tools indicate that the Mississippian Limestone interval of the Anadarko Shelf is unlikely to have generated liquid hydrocarbons because of lack of heightened productivity, and the largely terrestrial nature of organic matter preserved within the unit. Highlights: Paleoproductivity was not elevated during deposition of Mississippian Limestone. Detrital input was not elevated during deposition of Mississippian Limestone. Organic carbon isotope signatures within Mississippian Limestone sediments are largely terrestrial. Oil source rock potential of Mississippian Limestone sediments are equivocal due to lack of heightened paleoproductivity during sediment deposition.